Restaurant Liability for Contaminated Food and Beverages Pursuant to Negligence, Warranty, and Strict Liability Laws - Cavico, Frank J.; Mujtaba, Bahaudin G.; Muffler, Stephen; Samuel, Marissa; Polito, Nicolas- Michel (Global Journal of Social Sciences Studies, 2017)
Managers, owners and employees of all food providers must make sure that their products are safe, wholesome, and unadulterated prior to selling them. They must all be experts in making, storing, selling, preparing, and serving food. Otherwise, they could hurt consumers and face lawsuits since foodborne illnesses are a serious problem in the United States and around the world. Each year, about 48 million people in the United States suffer from foodborne illnesses that are linked to Salmonella, Norovirus, Listeria, and E. coli. This article examines three legal liability theories of negligence, warranty, and strict liability that are linked to contaminated food and beverages provided by restaurants. The authors end with recommendations to restaurant owners, employers, and managers on how to avoid liability by going above and beyond the law to provide quality food and beverages.